Inflammatory ringworm: a difficult diagnosis in black. - Chieco, P. (European Journal of Pediatric Dermatology, 2015)
The hair of black man is generally drier and more fragile than that of white and has a lower density (2). Different is especially the transverse section of the hair: the curly hair of the black usually has an elliptical cross-section, while in the white with straight hair has a round section. Probably because of these differences the ringworm of the scalp is more common in children of African immigrants in Europe and is more frequently caused by anthropophilic fungi of Trichophyton species. Among black children on mycological examination a positive culture from the scalp in the absence of clinical manifestations can be seen more easily (1). The presence of curly hair is blurring the margins of the lesions in hair diseases characterized by a regular round shape as ringworm and alopecia areata, or a linear shape as physiological hair loss of the newborn.